Answer:
2
Step-by-step explanation:
3*(-2)to power of 2 + 5*-2
= 3*4 + 5*-2
= 12 + -10 = 2
Assume N students
Student 1 can get (n-1) papers
Student 2 can get (n-1) papers
Student 3 can get (n-1) papers
etc
Student N can get (n-1) papers
So for N students you can have N(n-1)
Bring y to one side and the rest to the other switching the positives to negative then you’ll get Y=114
Answer:
21 savage
Step-by-step explanation:
Answer:
13
Step-by-step explanation:
13 right? all ya gotta do is add em together right?